Using activated and modified adsorbent surfaces from banana peels to remove the green Janus dye: : A Kinetic, Isothermal, and Thermodynamic Study (Mongolian Journal of Chemistry, 2024)
In order for the process of removing pollutants, including dyes, from the aquatic environment to be effective, plant wastes such as banana peels were used as adsorbent surfaces by thermally activating them (ABP) and modifying them with iron oxide nanoparticles (MABP), which were characterized using Fourier transform infrared (FT-IR) and X-ray diffraction (XRD) techniques. They were applied in the field of Janus green (JG) dye adsorption for the batch system and studied the effect of several factors (adsorbent weight, contact time, initial concentration, and temperature). Their data were analyzed kinetically using first- and second-order kinetic models and they were found to follow the second order. Their data were also analyzed through the equilibrium isotherms (Freundlich and Langmuir), and it was found to follow the Freundlich isotherm model. The thermodynamic functions for the dye adsorption process on both surfaces were calculated, through these functions, it was found that the dye adsorption process is spontaneous, easy, regular, and exothermic.